Strategi Pemasaran melalui Digital Marketing Berbasis E- Modul Flipbook untuk Kelompok Wanita Tani Desa Bedahlawak - Luluk Choirun Nisak Nur; Iin Baroroh Maarif; Mukhibaul Husnia (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
Bedahlawak village, is a village located in the northern part of the city of Jombang which is south of the Brantas river. Bedahlawak Village has a group or organization namely is Women Farmers Group (KWT) Saroja which is located in Bedah village. One of the programs in the Saroja KWT community is to utilize village land that has been neglected. The women of KWT Saroja were assisted by other villagers to work together to cultivate the land into fertile land and plant various kinds of vegetables. However, there are several obstacles faced by the women of KWT Saroja when the harvest season arrives, namely the abundant harvest but the sales are still manual door to door to local residents, so that many vegetables end up rotting because they are stored for too long. The purpose of this service is to provide knowledge as knowledge capital in developing production businesses through digital marketing and to increase the insight and awareness of partner participants on the benefits of digital marketing in this increasingly advanced era by using Electronic Modules (E Modules) as a means of written digital guidelines that make it easy people to be able to learn anytime and anywhere.